Decision-making in the system of protection of children and young people: A study comparing the attitudes of professionals and students - Delgado, Paulo (2018)
This study has as main objective to analyse the attitudes of 200 students of higher education and 200 professionals, responsible for case supervision and recommendations for intervention, in areas related to decision-making processes in the child and young people protection system, in matters such as foster care and residential care. The study adopts a quantitative strategy and data were collected in 2014 in the main regions of the country (Braga, Porto, Coimbra, Lisbon and Faro), with the application of the questionnaire “Child Welfare Attitudes Questionnaire” (Davidson-Arad & Benbenishty, 2008, 2010). The results show that both participants, professionals and students, can be divided into two groups, one more and other less favourable to removal. In comparison, professionals are less favourable to child’s removal and advocate reunification more than the students. There are no statistically significant differences between the participants regarding the role of foster and residential care, as well as the participation of the child in the decision-making process. However, professionals are more supportive of parental involvement in decision-making than students. Finally, there are some implications for practice.